Advokasi Grup Publik Facebook “Info Cegatan Jogja” dalam Pencegahan Aksi Premanisme “Klitih” di Yogyakarta, Indonesia - Surwandono Surwandono; Diana Mutiara Bahari (Society, 2020)
“Info Cegatan Jogja” is a popular public group on Facebook in informing social issues around Yogyakarta city, Indonesia. The information of netizens who get the most comments and responses is the gangsterism action known as “Klitih” in Yogyakarta. The term Klitih has been a street violence phenomenon that deeply disturbs the life of social, economic, education, and tourism in Yogyakarta. This study describes the role of the Facebook group “Info Cegatan Jogja” in advocating for the prevention of Klitih gangsterism in Yogyakarta. The analytical technique used was the mix method approach in the form of discourse analysis to capture the news dynamics and netizen responses to the phenomenon. The results of this study found that Facebook public group “Info Cegatan Jogja” can mobilize civilian awareness to participate and communicate intensively to encourage law enforcement officials to take firm action against their actions. The Facebook group “Info Cegatan Jogja” has become an important channel for community solidarity education in facing street violence “Klitih” in Yogyakarta.